Maternal Dietary Betaine Prevents High-Fat Diet-Induced Metabolic Disorders and Gut Microbiota Alterations in Mouse Dams and Offspring From Young to Adult - Liu, Jieying; Ding, Lu; Zhai, Xiao; Wang, Dongmei; Xiao, Cheng; Hui, Xiangyi; Sun, Tianshu; Yu, Miao; Zhang, Qian; Li, Ming; Xiao, Xinhua (Frontiers in Microbiology, 2022)
Early life is a critical window for preventing the intergenerational transmission of metabolic diseases. Betaine has been proven effective in treating glucose and lipid metabolism disorders. However, whether maternal betaine supplementation plays a role in regulating gut microbiota in both dams and offspring remains unclear. In this study, C57BL/6 female mice were fed with control diet (Ctr), high-fat diet (HF) and high-fat with betaine supplementation (0.3% betaine in the diet, HFB) from 3 weeks prior to mating and lasted throughout pregnancy and lactation. After weaning, the offspring got free access to normal chow diet until 20 weeks of age. We found that maternal dietary betaine supplementation significantly improved glucose and insulin resistance, as well as reduced free fatty acids (FFAs) concentration in dams and offspring from young to adult. When compared to HF group, Intestinimonas and Acetatifactor were reduced by betaine supplementation in dams, Desulfovibrio was reduced in 4 weeks old offspring of HFB group, and Lachnoclostridium was enriched in 20 weeks old offspring of HFB group. Moreover, the persistent elevated genus Romboutsia in both dams and offspring in HFB group was reported for the first time. Overall, maternal betaine could dramatically alleviate the detrimental effects of maternal overnutrition on metabolism in both dams and offspring. The persistent alterations in gut microbiota might play critical roles in uncovering the intergenerational metabolic benefits of maternal betaine, which highlights evidence for combating generational metabolic diseases.